Miss Todd and her wonderful flying machine - Poletti, Frances; Yee, Kristina (Compendium Inc., 2014)
"Miss Todd and her Wonderful Flying Machine is a work of fiction inspired by the real 1910 flight of a plane designed by Miss Lilian Todd. The story is set at the turn of the century when the world is awakening to the possibilities of the flying machine. One young woman, Miss Lily Todd, is inspired and she'll do whatever it takes to fly. But oh, no, no, no! At a time when becoming sky-born is already a challenge, Lily has more than gravity holding her down. Will she fly?"--Amazon.com.